Exploring the Adverse Impact of Smartphone Use on Young Individuals' Self-Esteem: A Structural Equation Modeling Approach based on Five Temperaments - Snegha, J.; Sudha, M. (Engineering, Technology & Applied Science Research, 2025)
Excessive Smartphone Use (ESU) has emerged as a major social concern, with widespread reliance on smartphones and the Internet resulting in various detrimental effects. This research aimed to analyze the primary psychological factors that affect ESU among individuals using Structural Equation Modeling (SEM). Smartphone addiction levels were evaluated using the Smartphone Addiction Scale, along with five different temperamental traits, namely, Depressive, Cyclothymic, Hyperthymic, Anxious, and Irritable, using the Affective Temperament Measure. Self-esteem was examined using the Rosenberg self-esteem scale. Of 376 participants aged 16 to 23, 88.4% showed signs of ESU, with certain temperamental traits being more prevalent. Negative impacts were especially noticeable among women. Self-esteem levels were found to be 15.7% high, 23.8% moderate, and 60.5% low. The results emphasize the harmful effects of excessive smartphone use on emotional and cognitive well-being, particularly in those with lower self-esteem. This study highlights the need to understand these relationships and create strategies to mitigate the negative effects of smartphone overuse.